Alternative Approaches: Implementing Mindfulness Practices in the Classroom to Improve Challenging Behaviors. (April 2019) - Zolkoski, Staci M.; Lewis-Chiu, Calli
Managing challenging student behaviors can be difficult for any educator. Lacking knowledge of research-based, positively oriented behavior interventions, educators may resort to punitive, reactive disciplinary strategies. Mindfulness is a positive, proactive approach that may help students with emotional and behavioral disorders improve their ability to regulate their own behaviors. This discussion paper describes research-informed mindfulness practices that teachers can use in their classrooms to address challenging behavior.